Allele distribution of D5S125, MAP1B5' and D5S679 microsatellite markers in Turkish spinal muscular atrophy families - Erdem, Hayat; Pehlivan, Sacide; Topaloğlu, Haluk; Togan, İnci; Özgüç, Meral (The Turkish Journal of Pediatrics, 1997)
Spinal muscular atrophy (SMA) is an autosomal recessive disease and one of the most common genetic causes of death in childhood. The gene for SMA has been mapped to chromosome 5q11.2-13.3. Chromosomal distribution of the alleles of D5S125, MAP1B5' and D5S679 polymorphic microsatellite markers in 14 unrelated Turkish SMA families have been determined. It is observed that the A9 allele of D5S679 has a significant (χ²: 3.41 p: 0.065) non-random association with mutant chromosomes.
Keywords: spinal muscular atrophy; microsatellite; polymorphism; non-random association